In-Depth Analysis Of The Experience Of Shallot Farmers In Implementing Ict-Based Marketing Strategies: A Case Study Of Increasing Product Marketability In Sukomoro Village, Nganjuk Regency - Indarsari , Savira Chalim; Subagyo (Universitas Nusantara PGRI Kediri, 2025)
Research Objectives: This research aims to deeply understand the experience of shallot farmers in Sukomoro Village, Nganjuk Regency, in implementing ICT-based marketing strategies. The main focus of the research is to uncover how the application of information and communication technology (ICT) affects the marketability of shallot products, increases farmers' income, and expands market reach.Design/Method/Approach: This research uses a descriptive qualitative method. Data was collected through interviews, observations, and document analysis by shallot farmers in Sukomoro Village, Nganjuk Regency. In this study, the data source came from several informants who had an understanding of marketing strategies in Sukomoro Village. Meanwhile, the object of the research is red bwang farmers.Research Findings: The findings in this study reveal that the application of ICT (Information, Communication, and Technology) based strategies has a significant effect on product sales and increasing the marketability of shallots in Sukomoro Village, Nganjuk Regency Theoretical/Originality Contribution: This research contributes to the literature on ICT-based marketing in the agricultural sector, especially on shallot commodities. The study also provides new insights into farmers' experiences in adapting to technology in specific local contexts. Practitioner/Policy Implications: The results of this study can be a reference for local governments in designing digital literacy training programs for farmers with the private sector for the development of ICT-based technology in the agricultural sector Limitations of the study: The study only focused on one village as a case study, so the results may not be fully generalizable to other regions. In addition, the study relies on interviews as the primary source of data, which can be influenced by the subjectivity of the respondents.